Establishing an indicator for measuring corporate market saturation (Research, Society and Development, 2022)
Understanding the competition and measuring its behavior are actions that can contribute to decision making in organizations. The construction of indicators based on open and easy-to-understand data allows for the understanding of the market reality and more assertive decision making. Thus, this paper aims to present a proposal for an indicator that enables the determination of the market saturation level. The methodological procedure used is action research with bibliographic and documental support. The indicator was applied experimentally in 155 municipalities that make up the southern region of Minas Gerais, with specific clippings for the municipality of Varginha. The results showed that the indicator proposed here allows the presentation of the most and least saturated sectors in a given locality. It was also evident that the calculations and analysis can occur in general terms per city and per region, as well as in more specific terms by sectors and between companies (business to business).